THE EFFECT OF HEAT AND MICROWAVE TREATMENTS ON ORANGE JUICE QUALITY DURING STORAGE - Thamer A. Khalil Khalil (Mesopotamia Journal of Agriculture, 2019)
The effect of heat and microwave (MW) treatments on quality related parameters as ascorbic acid (AA), browning index (BI), reducing sugar (RS), total soluble solid percentage (TSS %), and pH of orange juice (OJ) were investigated directly after the treatments and after storage at 4 and 20°C for 2 months. Microwave treatment induced little reduction in AA compared to heat treatment. Microwave treatment ensured the quality stability of orange juice stored for 2 months under refrigeration (4°C) but inferior orange juice quality was detected after 2 month storage at 20°C. Using MW exposure above 60 sec gave better studied parameters than heat treatments. However, microwave exposure for more than 60 sec. was sufficient to preserve the OJ quality. Accordingly, the use of microwave energy may be proposed as an alternative to traditional heat treatment in order to preserve the OJ quality.